Невизначеності через народження адронів у взаємодіях у кінцевому стані на нейтринній установці LBNF - Devi, R.; Singh, J.; Potukuchi, B. (Publishing house "Academperiodika", 2022)
Recent neutrino oscillation experiments used high atomic number nuclear targets to attain sufficient interaction rates. The use of these complex targets introduced systematic uncertainties due to the nuclear effects in the experimental observables and need to be measured properly to pin down the discovery. Through this simulation work, we are trying to quantify the nuclear effects in the argon (Ar) target in comparison to hydrogen (H) target which are proposed to be used at Deep Underground Neutrino Experiment far detector and near detector, respectively. Generated Events for Neutrino Interaction Experiments and NuWro, two neutrino event generators, are used to construct final state kinematics. To quantify the systematic uncertainties in the observables, we present the ratio of the oscillation probabilities (P(Ar)/P(H)) as a function of the reconstructed neutrino energy.